Dietary intake and body composition of prepubescent female aesthetic athletes - Soric, M.; Misigoj-Durakovic, M.; Pedisic, Z. (International Journal of Sport Nutrition and Exercise Metabolism, 2008)
The purpose of this study was to assess dietary intake and body composition of prepubescent girls competing in 3 aesthetic sports (artistic and rhythmic gymnastics and ballet). Because physiological demands of ballet training are similar to those in other aesthetic sports, ballet dancers were, for the purpose of this study, regarded as athletes. The sample consisted of 39 athletes (median age, 11 years, range 9-13) and 15 controls (median age, 11 years, range 10-12). Dietary intake was assessed using a quantitative food frequency questionnaire, and body composition, by means of anthropometry. There was no significant difference in total energy intake between groups, but there was a significant difference in energy substrate distribution. Artistic gymnasts reported significantly higher carbohydrate and lower fat contribution to total energy (57% ± 6% and 29% ± 5%, respectively) than rhythmic gymnasts (48% ± 6% and 36% ± 5%), ballet dancers (51% ± 4% and 34% ± 3%), or controls (51% ± 5% and 34% ± 4%). Relative to body weight, artistic gymnasts reported higher intake of carbohydrates (9.1 ± 4.2 g/kg) than rhythmic gymnasts (5.6 ± 3.1 g/kg), ballet dancers (6.6 ± 2.5 g/kg), or controls (5.4 ± 1.9 g/kg). Artistic gymnasts also had the lowest body-fat percentage among the groups. In all the groups mean reported daily intakes of most nutrients were higher than the current daily recommended intakes. The exceptions were dietary fiber and calcium. The proportion of athletes with an inadequate reported intake was highest for phosphorus (33%), followed by vitamin A and niacin (18%) and zinc (13%).